Analisa : Program Samsat Keliling Dan Samsat Drive Thru Dalam Menciptakan Kepuasan Wajib Pajak - Ida Fitriyah (Jurnal Profita: Komunikasi Ilmiah Akuntansi dan Perpajakan, 2023)
This study aims to examine the effect of mobile samsat and drive thru samsat on taxpayer satisfaction in paying taxes on two-wheeled motorized vehicles at the Lamongan samsat joint office. This research is a quantitative research with a descriptive approach. The population in this study uses an infinite population because the number of samples used cannot be known with certainty. The sampling technique used in this study is purposive sampling, from the technique obtained a research sample of 120 respondents. Data analysis using hypothesis testing. The data were analyzed using SPSS with SPSS 26 software. The results of the study with multiple linear regression analysis showed that the mobile samsat and drive thru samsat variables which became the dominant variable were samsat keliing, while using the F test showed that the mobile samsat and drive thru samsat variables had an effect on taxpayer satisfaction in paying two-wheeled motorized vehicle taxes at the Lamongan Samsat joint office.